Emerging Biologic Strategies in Crohn’s Disease - Natalia Niderla; Jakub Rzeszutek; Adrian Kubicki; Natalia Rachwał; Karolina Obuchowska; Dominika Grzybowska; Michał Kurnik; Adrianna Jaślikowska; Kamil Idzik; Weronika Grzyb (Journal of Education, Health and Sport, 2026)
Crohn’s disease is an inflammatory bowel disease, which substantially impairs patients’ quality of life. Despite ongoing advances, effective long-term management remains challenging in many cases. Conventional therapies are often associated with significant adverse effects and limited suitability for sustained use. This review provides an overview of the current landscape of novel biological therapeutics and their molecular targets. Several biologic therapies are already well established in clinical practice. Among them, IL-23 inhibitors stand out due to their high efficacy in both inducing and maintaining remission. Agents targeting the TL1A pathway, as well as human amniotic epithelial cells have shown promising early results and are currently under further investigation in clinical trials. Nevertheless, discontinuation of some biologics trials proves that not all theoretically attractive targets translate into meaningful clinical outcomes. Importantly, variability in efficacy can be observed even within the same class of drugs. This is exemplified by the success of upadacitinib in contrast to tofacitinib, which did not meet primary endpoints and was not further developed for this indication. Overall, these findings highlight both the progress achieved and the ongoing challenges in optimizing targeted therapies for Crohn’s disease.